URGENSI AKTA NOTARIS DALAM PERJANJIAN PENGALIHAN LISENSI RAHASIA DAGANG SEBAGAI UPAYA MEMBERIKAN KEPASTIAN HUKUM PARA PIHAK - Ferdiana, Herdy Ryzkyta; Amirulloh, Muhamad; Saleh, Kilkoda Agus (LITIGASI, 2021)
Confidential information or trade secrets of a company is very important for business actors, since the development of information-based business. Information has economic values and concerns the quality of the goods and services produced. If the transfer of trade secrets does not explicitly mention the existence of a connection with a Notary Deed, the interests of the parties in an agreement for the transfer of rights and trade secret licenses will lack of legal protection and ultimately create legal uncertainty. The notary deed serves as a means of proof in the event of a trade secret dispute for the parties involved. The power of proof of a notary deed as evidence is a perfect power of proof which then the notary deed must be recorded at the Directorate General of IPR. Keywords: legal certainty; trade secret; deed.